Study of Serum Lactate Dehydrogenase and Gamma-Glutamyl Transpeptidase in Breast Cancer Patients receiving Chemotherapy. - Anil Singh Basnyat; Abimanyu Jha; R Pathak; Bhupal Govinda Shrestha (Journal of Tropical Life Science, 2017)
Breast cancer (BC) is the most common type of cancer worldwide, being a major cause of morbidity in female. In Nepal it is the second most common type of cancer among females of perimenopausal age group. More than one quarter of the BC diagnosed in young Nepalese female, with familial history of breast cancer, early pregnancy, longer lactation and estrogen exposure and often with tumors showing aggressive biological behaviors. Anthracyclines (Doxorubicin) based treatment regime were reported to cause cardiotoxicity by increasing intramyocardial free radical production, lipid alterations and decreasing antioxidant level. Oxidative stress involving cellular reactive oxygen species (ROS) production is widely accepted mechanism but the molecular basis of chemotherapy induced organ toxicity remains highly controversial. An increased rate of metabolism and oxidative stress results rapid turnover of cancer cells that modulates the enzyme level in blood circulation. Serum LDH and GGT level correlates with tumor burden, metastatic character of BC and intensity of organtoxicity. The aim of our study is to evaluate the serum level of LDH and GGT in BC patients receiving chemotherapy and correlate these enzyme levels with different stages of BC. A total number of 150 subjects were included in the study, comprising 90 histopathologically confirmed 24 to 76 years aged patients of different breast cancer stages, receiving at least 3 cycles of 5-Fluorouracil, Adriamycin and Cyclophosphamide (FAC) chemotherapy. Sixty age- matched healthy women were enrolled as controls. Blood samples from each individual was collected after informed consent and analysed for serum LDH and GGT levels using standard biochemical methods. Data were analyzed using student's paired 't' test, Pearson correlation test and ANOVA. Serum LDH and GGT levels were significantly (p<0.001) increased in BC patients as compared to control group. When all 4 stages of BC were compared to control group, LDH and GGT showed steady and progressive increase in the activities of these enzymes from stage I-IV. The study concludes that serum LDH and GGT may be sensitive, specific and cost effective biomarkers in early diagnosis of breast cancer, assessing cancer prognosis and response to treatment.